FAKTOR-FAKTOR PENYEBAB STUNTING: LITERATURE REVIEW - Wahyu Aprilyaningsih; Bhisma Murti, Revi Gama Hatta Novika (CV. Adiba Aisha Amira, 2025)
Stunting is one of the health problems in developing countries, including Indonesia. Stunting is a condition where a child experiences growth disorders that are not in accordance with their age. The problem of stunting has an impact on the quality of human resources both in the short and long term. The study aims to determine the factors that cause stunting through a literature review. Some factors that cause stunting are: poor parenting practices; limited health services; still limited access to nutritious food by households/families; lack of access to clean water and sanitation; and infectious diseases.